Matriz de selección de completamientos múltiples (2018)
The technologies developed for reservoir management in the oil industry over time have allowed operating companies to increase their reserves. Some of these technologies are aimed at the development of stratified reservoirs, due to their differences in petrophysical properties or restrictions to flow together, it isn't profitable to produce them in a conventional way, so the implementation of multiple completions (intelligent, selective, dual, etc.) make the production of several reservoirs through the same well profitable. With the purpose of select candidate wells to obtain the maximum performance, a matrix of selection of multiple completions is created, which will give its recommendation based on the answers of a series of questions.